Screening, isolation and molecular characterization of pyrene degrading bacteria from oil sludge - Goh, Jennifer Kim Hoon (Universiti Malaysia Sarawak, UNIMAS, 2007)
In this study, total petroleum hydrocarbon (TPH) degrading bacteria were successfully isolated from oily sludge of Seria Crude Oil Terminal (SCOT), Brunei Darussalam. Suspected pyrene degrading bacteria selected by observing the bacterial growth and production of clear zones on MSM agar sprayed with 2 % pyrene solution. Three bacterial isolates were selected as pyrene degraders. From the preliminary biochemical tests and molecular identification using 16S rRNA sequences analysis, these selected bacteria were identified as Klebsiella pneumoniae (J1), Bacillus licheniformis (J2) and Bacillus cereus (J3). In addition, rate of pyrene degradation by these bacteria was also conducted by determine the total weight loss of pyrene after 2 months of bacterial incubation in MSM media with 1 % pyrene. The dry weight for pyrene was reduced by 49.17 % for Klebsiella pneumoniae, 45.83 % by Bacillus licheniformis and 50.83 % by Bacillus cereus. Meanwhile for motor oil degradation analysis, toluene assays were conducted to determine the percentage of remaining hydrocarbon based on optical density at 420 nm. After 30 days, 29.83 % and 32.69 % Motor oil hydrocarbon has been degraded by Bacillus licheniformis and Bacillus cereus, respectively.